Vitamin D-conjugated gold nanoparticles as functional carriers to enhancing osteogenic differentiation. Issue 1 (31st December 2019) - Nah, Haram; Lee, Donghyun; Heo, Min; Lee, Jae Seo; Lee, Sang Jin; Heo, Dong Nyoung; Seong, Jeongmin; Lim, Ho-Nam; Lee, Yeon-Hee; Moon, Ho-Jin; Hwang, Yu-Shik; Kwon, Il Keun
ABSTRACT: In an aging society, bone disorders such as osteopenia, osteoporosis, and degenerative arthritis cause serious public health problems. In order to solve these problems, researchers continue to develop therapeutic agents, increase the efficacy of developed therapeutic agents, and reduce side effects. Gold nanoparticles (GNPs) are widely used in tissue engineering applications as biosensors, drug delivery carriers, and bioactive materials. Their special surface property enables easy conjugation with ligands including functional groups such as thiols, phosphines, and amines. This creates an attractive advantage to GNPs for use in the bone tissue engineering field. However, GNPs alone are limited in their biological effects. In this study, we used thiol-PEG-vitamin D (SPVD) to conjugate vitamin D, an essential nutrient critical for maintaining normal skeletal homeostasis, to GNPs. To characterize vitamin D-conjugated GNPs (VGNPs), field emission transmission electron microscopy, energy dispersive X-ray spectroscopy, dynamic light scattering, and ultraviolet/visible absorption analysis were carried out. The developed VGNPs were well bound through the thiol groups between GNPs and vitamin D, and were fabricated in size of 60 nm. Moreover, to demonstrate VGNPs osteogenic differentiation effect, various assays were carried out through cell viability test, alkaline phosphatase assay, calcium deposition assay, real-time polymerase chain reaction, and immunofluorescence staining. As a result, the fabricated VGNPs were found to effectively enhance osteogenic differentiation of human adipose-derived stem cells (hADSCs) in vitro . Based on these results, VGNPs can be utilized as functional nanomaterials for bone regeneration in the tissue engineering field. Graphical abstract: uf0001